An Analysis of Code Switching Used By Maudy Ayunda in the YouTube Video “Study Hacks Ala Maudy Ayunda” - Hutabarat, Novra Melisa P.; Lumban Tungkup, Miranda Kristin; Hutabarat, Esra Delima; Silitonga, Sarah Priscilla; Simanjuntak, Kesmi Veronika; Sianturi, Bella Sonia; Pardede, Dwi Angeli; Samosir, Deswita Fitriani; Malau, Sara Stefani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study focuses on the phenomenon of code switching that appears in one of Maudy Ayunda's YouTube videos entitled